Norm Disharmony between Customary Law and Qanun in Nanggroe Aceh Darussalam - Gusti Agung Cahyono; Setiawan Budi; Rois Rahmawan (Universitas Trunodjoyo Madura, 2024)
In Indonesia, conflict over norms or disharmony in laws and regulations is a legal problem that often occurs. This is motivated by the existence of several legal mechanisms that overlap between the regulations below and the regulations above. As happened in Nanggroe Aceh Darussalam Province between customary law and positive law, which in this case is Qanun law. In this article, we will discuss efforts to harmonize norms between customary law and Qanun in Nanggroe Aceh Darussalam using descriptive qualitative methods. Efforts to resolve disharmony in statutory regulations are resolved by several alternatives, namely: 1) Right to Judicial Review of Legislative Regulations; 2) Constitutional Route; 3) Minister of Law and Human Rights Regulation Number 23 of 2018 concerning Harmonization of Draft Ministerial Regulations, Draft Regulations of Non-Ministerial Government Institutions, or Draft Regulations from Non-structural Institutions by Legislative Regulation Makers issued by the Ministry of Law and Human Rights; 4) Regulation of the Minister of Law and Human Rights Number 2 of 2019 concerning Resolving Disharmony in Legislative Regulations Through Mediation.